Regulation of cellular redox homeostasis in Arabidopsis thaliana seedling by atmospheric pressure cold plasma-generated reactive oxygen/nitrogen species - Dongjie Cui; Yue Yin; Hao Sun; Xiaojie Wang; Jie Zhuang; Lin Wang; Ruonan Ma; Zhen Jiao (Ecotoxicology and Environmental Safety, 2022)
Atmospheric pressure cold plasma (APCP) holds great potential as an efficient, economical and eco-friendly approach for improving crop production. Although APCP-induced plant growth promotion is undisputedly attributed to the reactive oxygen and nitrogen species (RONS), how these RONS regulate the intracellular redox state and plant growth is still largely unknown. This study systematically investigates the regulation mechanism of APCP-generated RONS on intracellular redox homeostasis in Arabidopsis thaliana seedling by measuring the RONS compositions in APCP-treated solutions and intracellular RONS and antioxidants in Arabidopsis seedlings. The results show that APCP exhibited a dual effect (stimulation or inhibition) on Arabidopsis seedling growth dependent on the treatment time. APCP-generated RONS in liquids increased in a time-dependent manner, leading to an increase of conductivity and oxidation reduction potential (ORP) and decrease of pH. APCP caused an enrichment of intracellular RONS and most of them increased with APCP treatment time. Meanwhile, APCP treatment accelerated malondialdehyde (MDA) generation, and the level of intracellular antioxidants were enhanced by low-dose APCP treatment while decreased at high doses. The results of correlation analysis showed that the extracellular RONS produced by APCP were positively correlated with the intracellular RONS and negatively correlated with the antioxidants. These results demonstrate that the improved antioxidant capacity induced by moderate APCP-generated RONS plays an important role in the growth promotion of Arabidopsis seedlings, which may be a promising alternative for fertilizers in agricultural production.